Nuclear compensatory evolution driven by mito-nuclear incompatibilities - Princepe, Debora; de Aguiar, Marcus A. M. (Proceedings of the National Academy of Sciences - PNAS, 2024)
Mitochondrial function relies on the coordinated expression of mitochondrial and nuclear genes, exhibiting remarkable resilience despite high mitochondrial mutation rates. The nuclear compensation mechanism suggests deleterious mitochondrial alleles drive compensatory nuclear mutations to preserve mito-nuclear compatibility. However, prevalence and factors conditioning this phenomenon remain debated due to its conflicting evidence. Here, we investigate how mito-nuclear incompatibilities impact substitutions in a model for species radiation. Mating success depends on genetic compatibility (nuclear DNA) and spatial proximity. Populations evolve from partially compatible mito-nuclear states, simulating mitochondrial DNA (mtDNA) introgression. Mutations do not confer advantages nor disadvantages, but individual fecundity declines with increasing incompatibilities, selecting for mito-nuclear coordination. We find that selection for mito-nuclear compatibility affects each genome differently based on their initial state. In compatible gene pairs, selection reduces substitutions in both genomes, while in incompatible nuclear genes, it consistently promotes compensation, facilitated by more mismatches. Interestingly, high mitochondrial mutation rates can reduce nuclear compensation by increasing mtDNA rectification, while substitutions in initially compatible nuclear gene are boosted. Finally, the presence of incompatibilities accelerates species radiation, but equilibrium richness is not directly correlated to substitution rates, revealing the complex dynamics triggered by mitochondrial introgression and mito-nuclear coevolution. Our study provides a perspective on nuclear compensation and the role of mito-nuclear incompatibilities in speciation by exploring extreme scenarios and identifying trends that empirical data alone cannot reveal. We emphasize the challenges in detecting these dynamics and propose analyzing specific genomic signatures could shed light on this evolutionary process.